CUL5-Mediated Visfatin (NAMPT) Degradation Blocks Endothelial Proliferation and Angiogenesis via the MAPK/PI3K-AKT Signaling. Issue 6 (December 2021) - Shi, Zanhua; Yao, Jiamei; Ma, Xinhua; Xu, Daomiao; Ming, Guangfeng
Abstract : Abstract: Endothelial dysfunction participates in the pathogenesis of various cardiovascular disorders, and dysregulated angiogenesis involves the vascular endothelial growth factor (VEGF)–matrix metalloproteinases (MMP) system. Nicotinamide phosphoribosyltransferase (NAMPT) is known to enhance endothelial function and angiogenesis. The study found that NAMPT overexpression protected human coronary artery endothelial cells (HCAECs) from H2 O2 -induced injury through promoting cell viability, inhibiting cell apoptosis, enhancing cell motility, and promoting tube formation. Through analyses based on 2 Protein–Protein Interaction databases, Mentha and BioGrid, we identified CUL5 as a protein that may interact with NAMPT, which was then validated by Co-IP experiments. Through interacting with NAMPT, CUL5 inhibited NAMPT expression. In contrast to NAMPT, CUL5 overexpression further aggravated H2 O2 -induced HCAEC dysfunction. In the meantime, CUL5 overexpression reduced, whereas NAMPT overexpression increased the phosphorylation of p38 and Akt and the protein levels of VEGF and MMP2. More importantly, NAMPT overexpression partially reversed the effects of CUL5 overexpression on H2 O2 -stimulated HCAECs and the MAPK/phosphatidylinositol 3-kinase-Akt/VEGF/MMP signaling. In conclusion, CUL5 interacts with NAMPT in H2 O2 -stimulated HCAECs, suppressing cell viability, promoting cell apoptosis, and inhibiting cell mobility and tube formation. NAMPT overexpression protects against H2 O2 -induced HCAEC dysfunction by promoting cell viability, inhibiting cell apoptosis, and enhancing cell mobility and tube formation.